The role of self-set goals in IS-enabled behavior change - Wörner, Anselma; Tiefenbeck, Verena (European Conference on Information Systems (ECIS 2018), 2018)
IS-enabled feedback interventions and self-tracking devices have shown to successfully induce behavior change in various professional and private domains. However, in particular for private contexts, the mechanisms that govern these processes are not well understood. Based on goal-setting theory, we identify self-set goals as a potential driver of behavior change induced by IS-enabled feedback. In a two-month field study, we provide activity-specific real-time feedback on resource consumption to 413 households and study the formation of self-set resource conservation goals in response. We chose showering as an example of an energy-intensive, habitual low-involvement target activity. The results suggest that IS-enabled real-time feedback successfully induces most individuals to set themselves a goal without exhortation, even for this kind of low-involvement activity. Against the predictions of goal-setting theory, we find that individuals tend to set themselves ambitious goals. In line with goalsetting theory, individuals who set themselves ambitious goals conserve more resources. Given the difficulty of defining adequate goals externally, and the risk of goal rejection and adverse reactions associated with externally assigned goals, the results suggest that personal IS should encourage users to self-set goals.<br